Fabrication of amorphous molybdenum sulfide/nitrogen-doped reduced graphene oxide nanocomposites with a tailored composition and hydrogen evolution activity via plasma treatment. (February 2022) - Zhang, Dai; Wang, Feilong; Fan, Xueliang; Zhao, Wenqi; Cui, Minghui; Li, Xuesong; Liang, Rongqing; Ou, Qiongrong; Zhang, Shuyu
Abstract: The development of efficient, scalable and cost-effective catalysts for the electrochemical hydrogen evolution reaction (HER) is essential for sustainable industrial-scale hydrogen generation via renewable energy. Recently, amorphous molybdenum sulfide (a-MoSx ) has emerged as a promising candidate; however, tuning the content of active S 2 2 − species in a-MoSx and enhancing its conductivity are vital for improving its HER activity. Herein, taking advantage of high reactivity at room-temperature and intrinsic nature of the concomitant reduction and etching effect of plasma, we report a facile, one-step method for fabricating amorphous molybdenum sulfide/nitrogen-doped reduced graphene oxide (N-RGO) nanocomposites as efficient and stable HER catalysts. The content of S 2 2 − species toward the HER can be readily controlled by varying the plasma treatment time, and the underlying mechanism was theoretically revealed by establishing and solving dynamic differential equations. Thus, the mechanism of tuning the HER activity of a-MoSx via compositional modulation was experimentally and theoretically unveiled. The optimal HER performance reached an overpotential of 168 mV at a current density of 10 mA cm −2 and a Tafel slope of 32 mV dec −1 at the maximal S 2 2 − content. This work provides a general route for fabricating amorphous transition metal chalcogenide/graphene nanocomposites as inexpensive, efficient and stable HER catalysts. Graphical abstract: Image 1